Testicular differentiation in 46,XX DSD: an overview of genetic causes - Ferrari, Maria Tereza Martins; Silva, Elinaelma Suelane do Nascimento; Nishi, Mirian Yumie; Batista, Rafael Loch; Mendonca, Berenice Bilharinho; Domenice, Sorahia (Frontiers in Endocrinology, 2024)
In mammals, the development of male or female gonads from fetal bipotential gonads depends on intricate genetic networks. Changes in dosage or temporal expression of sex-determining genes can lead to differences of gonadal development. Two rare conditions are associated with disruptions in ovarian determination, including 46,XX testicular differences in sex development (DSD), in which the 46,XX gonads differentiate into testes, and 46,XX ovotesticular DSD, characterized by the coexistence of ovarian and testicular tissue in the same individual. Several mechanisms have been identified that may contribute to the development of testicular tissue in XX gonads. This includes translocation of SRY to the X chromosome or an autosome. In the absence of SRY, other genes associated with testis development may be overexpressed or there may be a reduction in the activity of pro-ovarian/antitesticular factors. However, it is important to note that a significant number of patients with these DSD conditions have not yet recognized a genetic diagnosis. This finding suggests that there are additional genetic pathways or epigenetic mechanisms that have yet to be identified. The text will provide an overview of the current understanding of the genetic factors contributing to 46,XX DSD, specifically focusing on testicular and ovotesticular DSD conditions. It will summarize the existing knowledge regarding the genetic causes of these differences. Furthermore, it will explore the potential involvement of other factors, such as epigenetic mechanisms, in developing these conditions.